Analisis Kesadaran Petani Kopi Dalam Membayar Zakat Pertanian(Studi Kasus Desa Aromantai Kecamatan Pulau BeringinKabupaten Oku Selatan) - Veby Reza Fitria; Zuul Fitriani Umari; Abubakar Sidik; Peny Cahaya Azwari (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the level of awareness of coffee farmers in paying agricultural zakat and the factors that influence this awareness in Aromantai Village, Pulau Beringin District, South OKU Regency. Data were obtained through in-depth interviews with coffee farmers, religious leaders, and village officials as research informants. Data analysis techniques were carried out through the processes of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the level of awareness of coffee farmers in paying agricultural zakat in Aromantai Village is still relatively low. This is evident from the fact that coffee agricultural zakat has not yet become a routine obligation. Farmers generally only understand zakat in general and are more familiar with rice agricultural zakat than coffee agricultural zakat. Factors that influence the level of awareness of coffee farmers in paying agricultural zakat include low knowledge of the provisions of coffee agricultural zakat, community customs and culture, minimal socialization from religious leaders and zakat institutions, and the assumption that coffee agricultural zakat is not obligatory